A novel strategy to improving Rhodobacter azotoformans denitrification efficiency: Insight into the role of a two-component system NtrX/Y in denitrification regulation. (January 2023) - Qi, Zhengliang; Gao, Anxin; Li, Lu; Li, Zhen; Zhang, Wenyue; Dong, Shuhan; Liu, Xinli
Graphical abstract: Highlights: The ntrY is important for the denitrification of R. azotoformans . The NtrX/Y system regulates the nitrite reductase genes cluster expression. ntrY overexpression with iron supply optimization strengthens denitrification rate. Abstract: Transcription factors (TFs) can manage the coordinated expression of genes clusters or multiple genes. TF was used to improve bacterial denitrification ability in this study. During denitrification, the ntrY of R. azotoformans, which encodes the sensor of NtrX/Y system, was significantly upregulated in transcription. Denitrification of the mutant △ ntrY was significantly inhibited, and it was recovered after replenishing this gene to the mutant, which indicates the NtrX/Y system plays an important role in regulating bacterial denitrification. According to additional research, the NtrX/Y system regulates bacterial denitrification by directly promoting the expression of the nitrite reductase. ntrY overexpression appears to accelerate bacterial denitrification, and the introduction of a strong promoter tac in conjunction with iron supply optimization increases the rate by 72% further. This study realizes bacterial denitrification enhancement from the perspective of global transcription regulation, which provides a novel strategy for improving microbial ability to degrade pollutants.